2014
DOI: 10.1371/journal.pone.0107561
|View full text |Cite
|
Sign up to set email alerts
|

Differential Acute Postprandial Effects of Processed Meat and Isocaloric Vegan Meals on the Gastrointestinal Hormone Response in Subjects Suffering from Type 2 Diabetes and Healthy Controls: A Randomized Crossover Study

Abstract: BackgroundThe intake of meat, particularly processed meat, is a dietary risk factor for diabetes. Meat intake impairs insulin sensitivity and leads to increased oxidative stress. However, its effect on postprandial gastrointestinal hormone (GIH) secretion is unclear. We aimed to investigate the acute effects of two standardized isocaloric meals: a processed hamburger meat meal rich in protein and saturated fat (M-meal) and a vegan meal rich in carbohydrates (V-meal). We hypothesized that the meat meal would le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 51 publications
3
38
1
1
Order By: Relevance
“…This finding was also in agreement of study by Amini et al [20] and Fung [24]. Food components of meat and fats dietary pattern such as greater amounts of red meat, processed meat, butter, organ meat and hydrogenated meats might be account for higher triglyceride level; this was in consistent with the study by Belinova [25] reported a higher postprandial serum triglyceride concentrations after consuming processed meat compared with isocaloric vegan meal in patients with type 2 diabetes mellitus. However as shown in Table 3, patients in top quintiles of meat and fats dietary pattern had also significantly higher consumption of total dietary carbohydrate which might contribute in higher serum TG concentrations in these patients [26].…”
Section: Discussionsupporting
confidence: 92%
“…This finding was also in agreement of study by Amini et al [20] and Fung [24]. Food components of meat and fats dietary pattern such as greater amounts of red meat, processed meat, butter, organ meat and hydrogenated meats might be account for higher triglyceride level; this was in consistent with the study by Belinova [25] reported a higher postprandial serum triglyceride concentrations after consuming processed meat compared with isocaloric vegan meal in patients with type 2 diabetes mellitus. However as shown in Table 3, patients in top quintiles of meat and fats dietary pattern had also significantly higher consumption of total dietary carbohydrate which might contribute in higher serum TG concentrations in these patients [26].…”
Section: Discussionsupporting
confidence: 92%
“…Postprandially, we have not found any effects of both hypocaloric diet regimens on the response after the standard meal. According to previous studies, the initial postprandial response of PYY is supposed to be attenuated in patients with T2D [6], especially after a fatty meal [68]. The increased PYY3–36 response represents an improved capacity to regulate satiety and potentially body weight in insulin-resistant patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Its role in patients with T2D is uncertain. Some studies have shown higher fasting levels with blunted postprandial response, similar to PYY [68]. According to previous studies, peripheral administration of PP reduced food intake in lean healthy individuals [27].…”
Section: Discussionmentioning
confidence: 99%
“…Part of the association with CVD can be explained by the high levels of sodium (about 400% higher in processed meats) on blood pressure levels, and in addition processed meats such as sausages, have a higher content of SFA and cholesterol than fresh red meat . In addition, meat consumption was demonstrated to be associated with insulin resistance, abdominal obesity, the metabolic syndrome and oxidative stress . The observed risk for diabetes mellitus, and potentially for NAFLD, may be linked to several additional mechanisms including a role for; SFA, AGEs, nitrates/nitrites, heme iron, branched amino acids (BCAAs) based on data from clinical trials and animal models .…”
Section: The Association Between Individual Components Of the MD And mentioning
confidence: 99%